A teacher's perception of his professional role : a developmental study - Morwood, G E (Rhodes University, Faculty of Education, Department of Education, 1982)
This then was the object of this study, to determine 1) whether there is a pattern of attitude change common to teachers; II) whether early experience brings about different patterns of change among teachers; lll) whether specific life crises and events bring about these changes; lV) whether changes in attitudes occur at different stages in the teacher's career (Introduction, p. 12)
Keywords: Teachers -- Job satisfaction